PG118 Improving human factors around paediatric resuscitation during the COVID 19 pandemic. (10th November 2020) - Achaibar, Kira; Keating, Liza; A, Hussain; Jacques, Andrew; Callon, Vicky
Abstract : Background: Paediatric resuscitation and stabilisation is common in district general hospitals.1 This complex and often stressful situation involves medical and nursing teams from different specialties working collaboratively together. Early on in the COVID 19 pandemic an infant presented acutely with respiratory failure, cardiogenic shock and seizures. This case was challenging due to the clinical complexity, re-location of paediatric resuscitation facilities during the surge and the impact of personal protective equipment (PPE) on communication. We describe the use of in situ simulation and a locally adapted cognitive aid to enhance the delivery of paediatric resuscitation care during the global pandemic. Summary of Work: Since April 2020 we have run over 20 in situ paediatric emergency simulation scenarios initially thrice weekly for staff exposure to fortnightly sessions currently. Scenarios include paediatric sepsis, head injury, bronchiolitis or a recent paediatric case. On call teams from anaesthesia, critical care, emergency medicine and paediatrics are invited through the hospital paging system to attend a 'Paediatric Simulation Emergency Scenario' in the Emergency Department. Attendance is multi-disciplinary and usually involves 8–10 staff members per session. Scenarios incorporate the use of a locally developed Paediatric Emergency Intubation Checklist (figure 1 ) allowing a shared mental model of the COVID adaptions to intubation and ventilation. Simulation sessions last approximately 45 minutes including a debriefing section focused on communication and teamwork. Results and Discussion: Simulation training has allowed us to adapt paediatric resuscitation facilities improving access to the patient, visibility of monitoring, access to advanced airway and resuscitation equipment and designated areas for donning and doffing of PPE. Qualitative staff feedback suggests the impact of regular in situ simulation and a locally adapted intubation checklist improved confidence and communication within a team working in a new location during the global pandemic. Improving team performance is integral to improving patient safety and clinical care. Conclusion: We have used our understanding of human factors2 surrounding the case highlighted to inform quality improvement, change logistical process and promote ongoing learning and communication through simulation. References: Paediatric Intensive Care Society. Quality standards for the care of critically ill children. 2015 Systems Thinking for Everyday Work. A Safety Improvement Model for Healthcare. NHS Education for Scotland. 2018.